Drivers of land use-land cover changes in the Central Rift Valley of Ethiopia - Bekele, Belew; Wei, Wu; Yirsaw, Eshetu (Penerbit Universiti Kebangsaan Malaysia, 2019)
Land use-land cover change (LULCC) is driven by the interplay of forcing factors that act at global, regional, and local levels. Previous studies investigated mainly the basic socioeconomic drivers of LULCC. However, these studies less considered climate change vulnerability as a potential driver. Hence, this study is aimed to assess LULCC drivers in more fragile and dynamic landscapes of the East African Rift Valley region for the period of 1986-2016. We used a combination of Remote Sensing, Geographic Information System, logistic regression, and descriptive statistics to quantify and analyze the data. Image analysis results indicated that during the overall study period (1986-2016), grass/grazing land, agricultural land, and bare land have increased by 124%, 42%, and 34% respectively, whereas scattered acacia woodland, bush/shrubland, and swampy/marshy land have declined by 52%, 50%, and 31%, in that order. This image-derived change trend is in line with farmers’ perceived results. The top most influential drivers of LULCC includes population growth (95%), fuelwood extraction (93%), agricultural land expansion (92%), charcoal making (92%), climate change/recurrent drought (79%), and overgrazing (71%) in descending order of percentage of respondents. Education level and age of farmers significantly (p<0.05) affected their perception towards less perceived drivers. Hence, in order to reduce the adverse socio-environmental impacts of spectacular LULCC in the region, policy and decision makers need to take into account such principal drivers, particularly population growth and climate change.